2017
DOI: 10.1515/ijamh-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of music therapy on transition outcomes in adolescents and young adults with sickle cell disease

Abstract: Background The Build, Educate, Advance, Transition, in Sickle cell disease (BEATS) music therapy program was developed to address health challenges faced by adolescents/young adults (AYA) with sickle cell disease (SCD) during the transition to adult medical care. Objective The purpose of this study was to investigate the effects of BEATS on self-efficacy, trust, knowledge about SCD, and adherence in adolescents/young adults (AYA) with SCD. Subjects Thirty AYA with SCD, 18-23 years old, recruited from an adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Self-efficacy is related positively to fewer physical and psychological symptoms 36,58 and improved quality of life 59,60 among individuals with SCD. Urban African-American adolescent and young adult participants with SCD in a previous study of educational music therapy interventions 61 had slight improvements in self-efficacy (M = 1.73) from baseline to the end of the study, but these changes were not significant (p = 0.365). Whereas this prior study utilized interventions focused on educational goals such as medication management, understanding baseline lab values, and creating a pain action plan, MUSIQOLS provided music exercises targeted toward items in the SCSES such as reducing day-to-day pain, preventing symptoms from interfering with daily tasks, and improving sleep.…”
Section: Discussionmentioning
confidence: 77%
“…Self-efficacy is related positively to fewer physical and psychological symptoms 36,58 and improved quality of life 59,60 among individuals with SCD. Urban African-American adolescent and young adult participants with SCD in a previous study of educational music therapy interventions 61 had slight improvements in self-efficacy (M = 1.73) from baseline to the end of the study, but these changes were not significant (p = 0.365). Whereas this prior study utilized interventions focused on educational goals such as medication management, understanding baseline lab values, and creating a pain action plan, MUSIQOLS provided music exercises targeted toward items in the SCSES such as reducing day-to-day pain, preventing symptoms from interfering with daily tasks, and improving sleep.…”
Section: Discussionmentioning
confidence: 77%
“…Of these, four were primarily designed to assess feasibility of web modules, 29 virtual mentoring, 30 genetic education sessions, 31 and online patient portal. 32 Six studies assessed the impact of transition programs on psychosocial outcomes (self-efficacy, disease knowledge, transition readiness), [33][34][35][36][37][38] and one study looked at rate of transfer as a primary outcome. 39 Among the studies designed to test feasibility, four assessed the feasibility of electronic or mobile health-based programs, while the other two programs were conducted in person.…”
Section: Single-arm Pre/post Studiesmentioning
confidence: 99%
“…Only two studies reported completion rates, making it hard to compare rates of program completion among modalities. Four studies (one web-based and two in person) demonstrated improvements in disease knowledge postintervention, 29,[36][37][38] a program that utilized take-home worksheets demonstrated significant improvements in skill-building, 34 and a 6-month transition navigator program increased transition readiness among participants. 36…”
Section: Single-arm Pre/post Studiesmentioning
confidence: 99%
“…Central to music therapy practice is working collaboratively with patients and families to identify ways music can be used as a self-management strategy for procedural distress, treatment side effects, and social isolation that can result from extended hospitalizations and treatment. For example, Rodgers-Melnick et al (2019) created a group music therapy program to address health challenges faced by AYAs with sickle cell disease as they transition to adult medical care. Group drumming was used to promote cohesion and social support, followed by educational sessions that were co-facilitated with a medical provider.…”
Section: Music Therapy and The Psychosocial Standards Of Carementioning
confidence: 99%